Persons with Disabilities Act 2008: The Economic Promises for People with Disabilities? - Wahab, Harlida Abdul; Ayub, Zainal Amin (International Journal of Economics and Financial Issues, 2016)
People with disabilities (PWD) remain neglected in many areas including employment. Their unemployment rate is significantly high when compared with those without disabilities. Severe unemployment and poor wages ended majority of them live in poverty. PWD are suffering discrimination, social exclusion and prejudice. Realizing this fact and the needs for empowering their economy, life, wellbeing and social inclusiveness, PWD's rights has been exclusively acknowledged through the legislation namely Persons With Disabilities Act 2008 (the Act). This paper focuses on the laws and policies of the government of Malaysia in relations to the economic right of PWD that is employment. Special attention is given to the provisions relating to the “access of employment” as elaborated through the provisions of the Act. Discussion is also imparted on the policies and initiatives of government in supporting the position of disabled persons in employment. In examining this right, a doctrinal research approach is utilized whereby descriptive and exploratory studies are undertaken in order to describe the legal provisions and policies, as well as to determine the problems. The authors conclude that some parts of the law need to be reviewed for the empowerment and progress of the PWD. Believing that substantive law alone is inadequate in ensuring economic right of PWD, proper actions and appropriate plans are necessary to further enhance PWD's right and their surroundings. Keywords: Employment, Economy, Disability, Legislation, Policy; Right JEL Classifications: K10, K36